Acute upper gastrointestinal bleeding in the United Kingdom: improving outcomes - Jairath, V (2013)
Acute Upper Gastrointestinal Bleeding (AUGIB) accounts for 7000 deaths in the UK annually and is the single leading indication for transfusion of blood components. A large UK audit in 2007 reported high case fatality and rates of further bleeding. Since many deaths are determined by pre-existing co-morbidity, strategies to improve outcome should be targeted at preventable deaths and therefore focus upon improved control of haemorrhage and prevention of further bleeding, which are investigated in this thesis. Data for the analyses presented originate from the UK national audit of AUGIB, a laboratory study and a cross sectional survey. Five broad themes were investigated including service provision and timing of endoscopy, the use of transcatheter arterial embolisation (TAE) or surgery for refractory bleeding, the impact of coagulopathy on outcome, management of acute variceal haemorrhage (AVH) and haemostatic derangements after AVH, and the use of red blood cells (RBCs). Although there was no evidence of a “weekend effect” for mortality, earlier endoscopy (<12 hours) was associated with improved control of haemorrhage in higher risk patients compared to later endoscopy (>24 hours). TAE was an effective and safe modality for refractory bleeding, but the high post-surgical mortality (29%) raises questions about the appropriateness of case selection for surgery. Coagulopathy after non-variceal haemorrhage was associated with a 5-fold increase in risk-adjusted mortality. Further bleeding after AVH was strikingly high (26%) with notable deficiencies in the use of vasopressors, antibiotics and endotherapy. Global assessments of coagulation demonstrated that thrombin generation after AVH was normal, but clot strength was poor with excessive fibrinolysis. Platelets, fibrinogen and antifibrinolytics improved haemostasis ex vivo but coagulation factor transfusion had no effect. RBC transfusion practice is variable. This work on AUGIB provides new data highlighting areas of sub-optimal care, and informs both current practice and research questions for new interventional trials.